YTHDF1-mediated m6A modification of GBP4 promotes M1 macrophage polarization in acute lung injury - Fengan Cao; Shilei Wang; Qiuyue Tan; Junna Hou; Yunlu Li; Wentao Ma; Shilong Zhao; Jing Gao (Respiratory Research)
Abstract Background Acute lung injury (ALI) is a severe condition with multifaceted causes, including inflammation and oxidative stress. This research investigates the influence of m6A (N6-methyladenosine) modification on GBP4, a protein pivotal for macrophage polarization, a critical immune response in ALI. Methods Utilizing a mouse model to induce ALI, the study analyzed GBP4 expression in alveolar macrophages. By overexpressing or knocking down GBP4, the study assessed its impact on M1 macrophage polarization. The role of YTHDF1 was also explored through knockdown experiments to determine its effect on GBP4 expression and macrophage polarization. Results Increased GBP4 expression was noted in ALI model mice, promoting M1 macrophage polarization. YTHDF1 was found to enhance GBP4 expression by recognizing m6A sites on its mRNA, which was linked to reduced inflammation in MLE-12 cells upon YTHDF1 knockdown. Conclusion The study emphasizes the crucial roles of GBP4 and YTHDF1 in ALI development and immune response regulation. It suggests m6A modification as a potential therapeutic target, contributing to the understanding of ALI’s molecular mechanisms and guiding future treatment strategies.